Analisis Sistem Informasi Akademik STMIK Primakara Menggunakan User Experience Questionnaire (UEQ) - Si Gede Ngurah Kerta Sanjaya Arya Jelantik; I Putu Satwika; I Nyoman Yudi Anggara (STMIK Banjarbaru, 2019)
Abstract STMIK Primakara has an academic information system named Primakara Campus Information System / SISKA, but the system has not been validated through the user experience system, so it cannot be known to what extent user satisfaction is in its use. This paper analyzes the experience of students in using SISKA Primakara website media, through the User Experience test. The analytical method used in analyzing the user experience of this website is subjective analysis through interviews and distributing User Experience Questionnaire (UEQ) questionnaires to 202 Primkara STMIK students who have operated the SISKA website as respondents. The assessment was carried out on 6 aspects, namely: attractiveness, efficiency, perspicuity, dependability, stimulation and novelty. The analysis shows that the average respondent gives an impression with results above average (above average) on the scale of Clarity and Efficiency, as well as on the Attractiveness scale. However, Accuracy and Stimulation get below average results, so the novelty scale gets bad results. Keywords: Campus Information System, Academic Information System, User Experience, User Experience Questionnaire Abstrak STMIK Primakara memiliki sistem informasi akademik yang diberi nama Sistem Informasi Kampus (SISKA) Primakara, namun sistem tersebut belum divalidasi melalui sistem user experience, sehingga tidak dapat diketahui sejauh mana tingkat kepuasan user dalam penggunaannya. Paper ini menganalisa pengalaman mahasiswa dalam menggunakan media website SISKA Primakara, melalui uji User Experience. Metode analisis yang digunakan dalam menganalisis pengalaman pengguna website ini adalah analisis subjektif melalui wawancara dan menyebarkan kuesioner User Experience Questionnaire (UEQ) kepada 202 mahasiswa STMIK Primkara yang telah mengoperasikan website SISKA sebagai responden. Penilaian dilakukan pada 6 aspek yaitu: attractiveness, efficiency, perspicuity, dependability, stimulation dan novelty. Hasil analisis menunjukkan rata-rata responden memberikan impresi dengan hasil above average (di atas rata-rata) pada skala Kejelasan dan Efisiensi, serta pada skala Daya Tarik. Namun demikian, Ketepatan dan Stimulasi mendapatkan hasil below average (di bawah rata-rata), demikian dengan skala Kebaruan yang mendapatkan hasil bad (buruk). Kata kunci: Sistem Informasi Kampus, Sistem Informasi Akademik, User Experience, User Experience Questionnaire